Students’ Perception on The Use of Video Recording In Public Speaking Class - Syaninta Kusuma Aini; Sophia Binnendyk; Marlen Rijoly (International Journal of Education, Information Technology, and Others, 2022)
Video recording is used in Public Speaking class to cope with the new circumstances and condition of online learning during the spread of Covid-19 disease. This study was conducted to find out students' perceptions towards video recording in the public speaking class. Descriptive qualitative approach was chosen as the research design. There were two kinds of techniques of data collection: questionnaire and interview. The research involved 30 students of class 2021 who have taken the Public Speaking class in their second semester at Pattimura University. Students’perception will be analyzed through three aspects: Psyhological aspects, Academic aspects and Technical aspects. The result of this study showed that most of the students had positive perception on the use of video recording. Students admitted that video recording facilitate a better speaking practice which in turn help them to improve their speaking and they feel that they can achieve the learning competencies (Academic aspects). The students also considered the process of making video recording as fun, and exciting (Psychological Aspect). Students also felt there is no significances difficulty in the process of making the video (Technical aspect). In light of the findings, video recording is considered a favorable and effective media for students in Public Speaking course